International tax reform and FDI - Pierce O'Reilly (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
The taxation of multinational enterprises is a key policy issue that has major impacts on global FDI flows. This Perspective reviews the recently published Economic Impact Assessment of the ongoing OECD/G20 Inclusive Framework on BEPS process to address the tax challenges of the digitalization of the economy.
Keywords: 330